Managing Metastatic Thymoma With Metabolic and Medical Therapy: A Case Report - Phillips, Matthew C. L.; Murtagh, Deborah K. J.; Sinha, Sanjay K.; Moon, Ben G. (Frontiers in Oncology, 2020)
Thymomas consist of neoplastic thymic cells intermixed with variable numbers of non-neoplastic lymphocytes. Metastatic thymomas are typically managed with non-curative chemotherapy to control tumor-related symptoms; no prolonged survival is expected. Metabolic-based approaches, such as fasting and ketogenic diets, target cancer cell metabolism by creating an increased reliance on ketones while decreasing glucose, glutamine, and growth factor availability, theoretically depriving cancer cells of their metabolic fuels while creating an unfavorable environment for cancer growth, which may be beneficial in metastatic thymoma. We report the case of a 37-year-old woman with myasthenia gravis, diagnosed with an inoperable type AB, stage IVA thymoma, who pursued a metabolic intervention consisting of periodic fasting (7-day, fluid-only fasts every 1–2 months), combined with a modified ketogenic diet on feeding days, for 2 years. Fasting-related adverse effects included cold intolerance, fatigue, and generalized muscle aches, all of which resolved during the second year. She experienced two myasthenia relapses, each associated with profoundly reduced oral intake, marked weight loss, and tumor regression-the first relapse was followed by a 32% decrease in tumor volume over 4 months, the second relapse by a dramatic 96% decrease in tumor volume over 4 months. The second relapse also required prednisone to control the myasthenia symptoms. We hypothesize that 2 years of fasting and ketogenic diet therapy metabolically weakened the neoplastic thymic cell component of the thymoma, “setting the stage” for immune activation and extreme energy restriction to destroy the majority of cancer cells during both relapses, while prednisone-induced apoptosis eradicated the remaining lymphocytic component of the thymoma during the second relapse. This case is unique in that a metabolic-based fasting and ketogenic diet intervention was used as the primary management strategy for a metastatic cancer in the absence of surgery, chemotherapy, or radiotherapy, culminating in a near-complete regression. Nearly 3 years after being diagnosed with inoperable metastatic cancer, our patient shows no signs of disease and leads a full and active life.